Investasi Dengan Sistem Build Operate And Transfer (Bot) Perspektif Hukum Islam (Studi di Rumah Makan Pindang Uwo Sumur Putri Bandar Lampung) - Sukmawati, Rini; Liyorba Indra, Gandhi; Huriyah, Ida Khoridah (Universitas Islam Negeri Raden Intan Lampung, 2022)
An agreement is a deal made between somebody or some person with somebody or other people to do a deed certain. If this observed, that the agreement made by the two parties will basically give rise to a right on the one hand, and an obligation on the other. This is closely related to the existing legal aspect. So that is in law if something deed has influence or consequence which related to a law called with deed law (including agreement). The problem in the study is how to form an agreement to work on the same among owner soil with manager House Eat and How View Law Islam to implementation cooperation Build Operate and Transfer (BOT) in development and management House Eat as the place effort. Destination from the study this that is for knowing form agreement work same Among owner soil with manager House Eat and for knowing View Law Islam to implementation cooperation Build Operate and Transfer (BOT) in development and management House Eat as the place effort. Type study which used in a study this is study field (Field Research) that is something studies which conducted in environment Public certain, good in institutions organization Public (social), nor institution government. Source data obtained from the study direct and obtained from a source other like dark books about the agreement, journals, and source Al- Qur'an and hadith about the agreement. Based on description on study this could take conclusion that is Form agreement cooperation Build Operate And Transfer (BOT) which set in Regulation Minister In Country No. 19 Year 2016 About Guidelines Management Goods Owned by Area, on base agreement No.511.3/11297, No.007/OIM/VII/ 2004 Among holder power soil in Thing this owner soil with manager house eat or perpetrator effort which will set up effort on soil owner soil building with notes will give part profit results business to government and later will return object agreement in the form of soil to owner soil if time which agreed already finished. Cooperation system Build Operate And Transfer (BOT) which conducted by owner soil and manager house eat based on get along and condition which already in do already Fulfill sharia Islam where second party each other profitable and To do Thing Halal in accordance with provision Islamic law. Keywords: BOT, Islamic Law, Investation, System